2013
DOI: 10.1017/s0317167100012993
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Bilirubin with Stroke Severity and Clinical Outcomes

Abstract: Objective:The aim of the study is to explore the association of serum bilirubin levels with admission severity and short term clinical outcomes among acute ischemic stroke patients.Methods:Data were collected from 2361 acute ischemic stroke patients in four hospitals of Shangdong Province during January 2006 and December 2008. National Institutes of Health Stroke Scale (NIHSS) was used to assess admission and discharge severity. NIHSS≥10 at discharge or in-hospital death was defined as short-term clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…19,20 Collectively, the evidence from this 18 and other studies [11][12][13][14][15][16][17] supports the possibility that the early measurement of TB levels might be useful to assess the risk of silent cerebral infarction(s) and major stroke and that mildly elevated TB levels might protect from stroke events and from neurological damage in stroke.…”
Section: Targher Risk Of Ischemic Stroke 703supporting
confidence: 57%
See 1 more Smart Citation
“…19,20 Collectively, the evidence from this 18 and other studies [11][12][13][14][15][16][17] supports the possibility that the early measurement of TB levels might be useful to assess the risk of silent cerebral infarction(s) and major stroke and that mildly elevated TB levels might protect from stroke events and from neurological damage in stroke.…”
Section: Targher Risk Of Ischemic Stroke 703supporting
confidence: 57%
“…13 Few recent studies that have explored the association of TB levels with the severity and subtypes of stroke among hospitalized patients with a first-ever acute ischemic stroke have shown that patients with mildly higher TB levels had a significantly greater admission severity of stroke (as assessed by the National Institutes of Health Stroke score), but not short-term clinical outcomes (ie, in-hospital death or National Institutes of Health Stroke score ≥10), than those with lower TB levels. [14][15][16] In a retrospective study of 626 patients with acute ischemic stroke, Zhang et al 17 reported that mildly higher TB levels at admission were associated with an increased odds for nonlacunar ischemic stroke. It is possible to assume that higher TB levels after acute ischemic stroke reflect the intensity of the initial oxidative stress induced by the neurological damage.…”
Section: See Accompanying Article On Page 946mentioning
confidence: 99%
“…Earlier researches have demonstrated an inverse correlation between serum bilirubin and the risk of coronary artery disease and decreased antioxidant activity of bilirubin in atherosclerotic lesions [1, 2]. Recent studies have confirmed the correlation between serum bilirubin levels and collateral development in patients with chronic total coronary occlusion [3], peripheral arterial disease [4], amputation events in type-2 diabetes mellitus [5], stroke severity and clinical outcomes [6]. Those results suggested that bilirubin may be a part of a cell defense strategy in those macro- and micro- angiopathies.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al reported that serum levels of DBIL and TBIL were increased after AIS, which was linked to the severity of stroke. Other studies demonstrated the positive correlation between TBIL, DBIL and the NIHSS of ischemic stroke patients [54,55]. It was also found that TBIL, DBIL and IBIL levels were signi cantly associated with mortality in AIS patients [56].…”
Section: Subgroup and Meta-regression Analysesmentioning
confidence: 85%